Ethics in Marketing-the Need of the Hour - Srivastava, Chetan (Indian Journal of Marketing, 2005)
When we think about marketing, a funny and popular anecdote always comes to our mind. The anecdote really provokes thought, even though it is only humor, it goes like this. A marketing Manager dies 'and he is at the eternal gates, where the master has to decide, whether he is to be sent to Hell or Heaven, looking at his tract record, master decides to give him a chance to choose between Heaven and Hell. Taking the Oppourtunity, the marketing manager asks the master to practically look at both the places, before he makes a choice, which seems to be fair enough and the master agrees.